Aluminum-based composite material and preparation method thereof

By adding silicon carbide particles to the aluminum chips and adopting high-temperature pressing and hot extrusion processes, the problems of complex and high cost of the existing aluminum-based composite materials are solved, and the mechanical properties and process simplification of the aluminum-based composite materials are achieved.

CN119710342APending Publication Date: 2025-03-28GUANGDONG ZHONGSE YANDA NEW MATERIAL TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411925868.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The preparation process of existing aluminum-based composite materials is complex, has high cost, and its performance in resistance to deformation and elastic deformation is not as good as stainless steel and titanium alloys.

Method used

By adding silicon carbide particles to the aluminum chips and using high temperature pressing and hot extrusion processes, an aluminum-based composite material with high yield strength, elastic modulus and plasticity was prepared.

Benefits of technology

The excellent mechanical properties of aluminum-based composite materials are achieved, with a yield strength of ≥400MPa, elastic modulus ≥85GPa, and plasticity ≥8%. At the same time, the preparation process is simplified and the cost is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005209239290000061
    Figure BDA0005209239290000061
Patent Text Reader

Abstract

The invention discloses an aluminum-based composite material and a preparation method thereof. The aluminum-based composite material comprises the following components in percentage by mass: 0.9 to 1.5 weight percent of Mg, 0.9 to 1.5 weight percent of Si, 0.6 to 1.1 weight percent of Cu, 0.01 to 0.15 weight percent of Mn, 0.01 to 0.15 weight percent of Cr, less than or equal to 0.03 weight percent of Ti, less than or equal to 0.10 weight percent of Fe and the balance of Al and inevitable impurity aluminum scraps; the aluminum skimmings and the silicon carbide particles are vibrated and mixed according to the mass ratio of (95-99.9): (0.1-5), then the mixture is placed in a briquetting machine to be pressed into an aluminum bar blank at high temperature, and finally the aluminum bar blank is placed in an extruding machine to be subjected to hot extrusion. According to the aluminum-based composite material prepared through the method, the yield strength is larger than or equal to 400 MPa, the elastic modulus is larger than or equal to 85 GPa, and the plasticity is larger than or equal to 8%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of aluminum alloys, and in particular to an aluminum-based composite material and a preparation method thereof. Background Art

[0002] Compared with stainless steel and titanium alloys, aluminum alloys are widely used in the production of various product components due to their light weight, medium strength, strong recyclability, and good thermal conductivity. However, under the same strength conditions, stainless steel and titanium alloys have a higher elastic modulus (stainless steel elastic modulus ~200GPa, titanium alloy elastic modulus ~100GPa), so they are better in resisting deformation, especially elastic deformation. For aluminum alloys, the elastic modulus of 7 series aluminum alloys is slightly higher than that of 6 series aluminum alloys, ~2GPa, but both are around 70GPa, which is much smaller than the elastic modulus of stainless steel and titanium alloys. The elastic modulus is a characteristic property of the material, and the alloy composition or processing technology has little effect on it. CN202210566156.0 provides an aluminum-based composite material with added particles. The invention increases the elastic modulus to ~80GPa by adding 0.1-7wt.% of external reinforcing particles such as carbon fiber, carbon nanotubes, graphene or aerogel particles during the casting process of 6 series aluminum alloys. However, since the reinforcing particles are added during the casting process, it is easy to cause the reinforcing particles to segregate or sink to the bottom of the furnace, and thus cannot be truly added to the matrix. CN202411558034.2 provides an aluminum-based composite material containing Gd and a preparation method thereof, which uses a ball milling method to prepare the raw materials and is sintered by hot isostatic pressing. However, this method requires special equipment and is relatively costly, so the material is mainly used in military industry or special industries. CN202411472692.X provides an aluminum-based composite material containing nano-Ti particles and graphene nanosheets and a preparation method thereof. The method comprises: dispersing nano-Ti particles, graphene nanosheets and aluminum matrix powder in an acetone solution to obtain a mixed slurry; vacuum drying the obtained mixed slurry to obtain a solid composite powder; ball-milling the solid composite powder to obtain ball-milled aluminum-based composite particles; pressure sintering the ball-milled aluminum-based composite particles under vacuum or high-purity argon to finally prepare an aluminum-based composite material. This method also has the problems of complex preparation process and high manufacturing cost. CN202411272806.6 provides an aluminum-based composite material and a preparation method thereof: 1) mechanically alloying an aluminum-nickel amorphous alloy, a rare earth reinforcement material and a portion of an aluminum-nickel matrix alloy to obtain an amorphous rare earth alloy reinforcement; 2) mixing nano aluminum and nano nickel oxide powders and pressing them into a blank; 3) subjecting the aluminum and nickel oxide in the blank to an aluminothermic reaction to generate nano aluminum oxide and nano nickel powders; 4) melting the remaining portion of the aluminum-nickel matrix alloy into an aluminum alloy melt, adding nano aluminum oxide and nano nickel powders and melting them in the aluminum alloy melt; 5) pouring the aluminum alloy melt obtained in step 4 into the amorphous rare earth alloy reinforcement, cooling and solidifying, and obtaining a reinforced aluminum-based composite material. This method also has the problems of complicated process, high cost and unsuitability for large-scale mass production. Therefore, it is necessary to invent an aluminum-based composite material and its processing technology with simple process and excellent performance. Summary of the invention

[0003] The purpose of the present invention is to provide an aluminum-based composite material and a preparation method thereof in view of the deficiencies in the prior art. The preparation process is simple and the obtained aluminum-based composite material has excellent mechanical properties.

[0004] The purpose of the present invention is achieved through the following technical solutions:

[0005] First, the present invention provides a method for preparing an aluminum-based composite material, which specifically comprises:

[0006] Weigh silicon carbide particles and aluminum chips according to the mass ratio of (0.1-5): (95-99.9);

[0007] The aluminum chips are degreased and vibrated and mixed with the silicon carbide particles, and then the mixture is placed in a briquetting machine and pressed at high temperature into aluminum rod blanks. Finally, the aluminum rod blanks are placed in an extruder for hot extrusion.

[0008] Furthermore, the particle size of the aluminum chips is ≤5 mm, and the particle size of the silicon carbide particles is 0.1-1 mm.

[0009] Furthermore, the aluminum chips include the following raw material components in mass percentage: Mg 0.9-1.5wt.%, Si 0.9-1.5wt.%, Cu 0.6-1.1wt.%, Mn 0.01-0.15wt.%, Cr 0.01-0.15wt.%, Ti≤0.03wt.%, Fe≤0.10wt.%, and the balance is Al and unavoidable impurities, wherein the mass ratio of Mn to Cr in the aluminum chips is (1-1.5):1.

[0010] Furthermore, the vibration mixing adopts a powder resonance mixer, and the vibration frequency of the powder resonance mixer is 20-30 Hz and the vibration time is 15-30 min.

[0011] Furthermore, the specific process of placing the mixture in a briquetting machine to press it into aluminum rod blanks is as follows: the mixture of silicon carbide particles and aluminum chips is loaded into the mold of the briquetting machine, the pressure of the briquetting machine is 1-5 tons, the mold temperature during the pressurization process is 400-520°C, and the pressurization time is 1-5 minutes.

[0012] Furthermore, the hot extrusion process is as follows: placing the aluminum rod blank in an extruder, and extruding the aluminum rod blank under the conditions of an extrusion ratio of 15-30, an extrusion temperature of 540-570° C., and an extrusion speed of 2-4 m / min.

[0013] Furthermore, the aluminum chips degreasing and degreasing process is: the aluminum chips are ultrasonically cleaned using a strong alkaline solvent, a surfactant and acetone in sequence, and finally cleaned with ethanol, and dried for later use;

[0014] The ultrasonic cleaning is performed with an ultrasonic power of 100-500W and a cleaning time of 10-30 minutes.

[0015] Secondly, the present invention provides an aluminum-based composite material, which is prepared by the above-mentioned method for preparing the aluminum-based composite material, and the yield strength of the aluminum-based composite material is ≥400MPa, the elastic modulus is ≥85GPa, and the plasticity is ≥8.

[0016] The beneficial effects of the present invention are:

[0017] In 6 series aluminum alloys, Mg, Si, and Cu elements are the main added elements. Their content levels determine the mechanical properties of the material. The greater the addition amount, the higher the strength. However, if the content is too high, it will affect the deformation processing efficiency and will not help the elastic modulus. Therefore, the content of Mg, Si, and Cu should be 0.9-1.5wt.% for Mg, 0.9-1.5wt.% for Si, and 0.6-1.1wt.% for Cu.

[0018] Mn and Cr are trace elements, which mainly control the grain size. Especially in the high-temperature pressing and extrusion process of the mixture of aluminum chips and SiC, the appropriate addition of Mn and Cr can hinder the growth of grains, and the fine compounds formed by Mn and Cr can also hinder the aggregation of SiC particles in the preparation process of composite materials. The content of Mn is 0.01-0.15wt.%, and Cr is 0.01-0.15wt.%. At the same time, when Mn / Cr=1-1.5, the resistance to grain boundary migration and segregation of SiC particles is more significant.

[0019] Ti and Fe are trace impurity elements and can be controlled within the required range: Ti≤0.03wt.%, Fe≤0.10wt.%.

[0020] The above-mentioned aluminum chips with a particle size of ≤5mm are vibrated and mixed with SiC particles with a particle size of 0.1-1mm after being deoiled and degreased, and then the mixture is placed in an aluminum chip briquetting machine to be pressed into aluminum rod blanks, and then extruded; the particle sizes of aluminum chips and SiC particles are limited in the present invention in order to obtain better composite effects and higher mechanical properties.

[0021] In the above preparation process, the aluminum bar blank is pressurized for 1-5 minutes during the pressing process, and the mold is kept warm at 400-520°C during the pressing process. This process is actually a process of physical combination of aluminum chips and reinforcing particles. By controlling the pressing time and temperature, SiC and aluminum chips are fully combined and the aluminum chips are fully diffused, which is beneficial to subsequent extrusion. If the combination of SiC, aluminum chips, and aluminum chips is poor in this step, the extruded blank cannot be extruded in the subsequent extrusion process, and the blank is easy to break into powdery substances during the extrusion process;

[0022] The prepared aluminum billet is extruded into a billet with an extrusion ratio of 15-30, an extrusion temperature of 540-570°C, and an extrusion speed of 2-4 m / min. During the extrusion process, the extrusion ratio, extrusion temperature, and speed are controlled to increase the density of the billet, reduce the porosity, and promote the forming of the material.

[0023] By the above method, an aluminum-based composite material with a yield strength of ≥400 MPa, an elastic modulus of ≥85 GPa, and a plasticity of ≥8% can be prepared. DETAILED DESCRIPTION

[0024] In order to further understand the present invention, preferred embodiments of the present invention are described below in conjunction with examples. However, it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, rather than limiting the claims of the present invention.

[0025] Example 1

[0026] Aluminum chips with a particle size of 5 mm are taken, and the aluminum chips include the following components by mass percentage: 1.5wt.% of Mg, 0.9wt.% of Si, 1.1wt.% of Cu, 0.1wt.% of Mn, 0.1wt.% of Cr, 0.03wt.% of Ti, 0.10wt.% of Fe, and the balance is Al and inevitable impurities; the aluminum chips are ultrasonically cleaned for 20 minutes using 3mol / L sodium hydroxide solution, 10wt.% alcohol ether phosphate solution and acetone in sequence, with an ultrasonic power of 200W, and finally cleaned with ethanol, and dried for use;

[0027] The cleaned aluminum chips and silicon carbide particles with a particle size of 0.1 mm were placed in a powder resonance mixer at a mass ratio of 99.9:0.1 for vibration mixing. The vibration frequency of the powder resonance mixer was 30 Hz and the vibration time was 20 min.

[0028] The mixture of silicon carbide particles and aluminum chips is filled into the mold of the briquetting machine and pressed for 1 minute at a pressure of 3 tons. During the pressing process, the mold is kept at 520°C to obtain an aluminum rod blank.

[0029] The aluminum rod blank is placed in an extruder, and the aluminum rod blank is extruded under the conditions of an extrusion ratio of 15, an extrusion temperature of 570° C., and an extrusion speed of 2 m / min to obtain an aluminum-based composite material.

[0030] Example 2

[0031] Aluminum chips with a particle size of 3 mm are taken, and the aluminum chips include the following components by mass percentage: 0.9wt.% of Mg, 1.5wt.% of Si, 0.6wt.% of Cu, 0.15wt.% of Mn, 0.1wt.% of Cr, 0.01wt.% of Ti, 0.08wt.% of Fe, and the balance is Al and inevitable impurities; the aluminum chips are ultrasonically cleaned for 20 minutes using 3mol / L sodium hydroxide solution, 10wt.% alcohol ether phosphate solution and acetone in sequence, with an ultrasonic power of 200W, and finally cleaned with ethanol, and dried for use;

[0032] The cleaned aluminum chips and silicon carbide particles with a particle size of 1 mm were placed in a powder resonance mixer at a mass ratio of 95:5 for vibration mixing. The vibration frequency of the powder resonance mixer was 30 Hz and the vibration time was 20 min.

[0033] The mixture of silicon carbide particles and aluminum chips is filled into the mold of the briquetting machine and pressed for 5 minutes at a pressure of 3 tons. During the pressing process, the mold is kept at 400°C to obtain an aluminum rod blank;

[0034] The aluminum rod blank is placed in an extruder, and the aluminum rod blank is extruded under the conditions of an extrusion ratio of 30, an extrusion temperature of 540° C., and an extrusion speed of 4 m / min to obtain an aluminum-based composite material.

[0035] Example 3

[0036] Aluminum chips with a particle size of 2 mm are taken, and the aluminum chips include the following components by mass percentage: Mg 1.1wt.%, Si 1.2wt.%, Cu 0.8wt.%, Mn 0.10wt.%, Cr 0.09wt.%, Ti 0.009wt.%, Fe≤0.08wt.%, and the balance is Al and inevitable impurities; the aluminum chips are ultrasonically cleaned for 20 minutes using 3mol / L sodium hydroxide solution, 10wt.% alcohol ether phosphate solution and acetone in sequence, with an ultrasonic power of 200W, and finally cleaned with ethanol, and dried for use;

[0037] The cleaned aluminum chips and silicon carbide particles with a particle size of 0.8 mm were placed in a powder resonance mixer at a mass ratio of 98.8:1.2 for vibration mixing. The vibration frequency of the powder resonance mixer was 30 Hz and the vibration time was 20 min.

[0038] The mixture of silicon carbide particles and aluminum chips is filled into the mold of the briquetting machine and pressed for 3 minutes at a pressure of 3 tons. During the pressing process, the mold is kept at 480°C to obtain an aluminum rod blank.

[0039] The aluminum rod blank is placed in an extruder, and the aluminum rod blank is extruded under the conditions of an extrusion ratio of 25, an extrusion temperature of 560° C., and an extrusion speed of 3 m / min to obtain an aluminum-based composite material.

[0040] Comparative Example 1

[0041] The composition of the aluminum-based composite material in Comparative Example 1 is consistent with that in Example 1, except that:

[0042] The above-mentioned aluminum chips with a particle size of 5 mm are vibrated and mixed with silicon carbide particles with a particle size of 0.1 mm after degreasing and deoiling, and then the mixture is placed in an aluminum chip briquetting machine to be pressed into aluminum rod blanks. The pressure is applied for 6 minutes at a pressure of 3 tons. During the pressing process, the mold is kept warm at 300°C and then hot extrusion is performed.

[0043] In Comparative Example 1, the extruded billet was powdered during the hot extrusion process and could not be formed.

[0044] Comparative Example 2

[0045] The composition of the aluminum-based composite material in Comparative Example 2 is consistent with that in Example 1, except that:

[0046] The above-mentioned aluminum chips with a particle size of 5 mm are deoiled and degreased, then vibrated and mixed with SiC particles with a particle size of 0.1 mm, and then the mixture is placed in an aluminum chip briquetting machine to be pressed into aluminum rod blanks, and pressed for 1 minute at a pressure of 3 tons. During the pressing process, the mold is kept warm at 520°C, and then hot extrusion is performed with an extrusion ratio of 15, an extrusion temperature of 570°C, and an extrusion speed of 5 m / min.

[0047] In Comparative Example 2, the extruded material cracked during the hot extrusion process and partly turned into powder.

[0048] According to the standard GB / T6892-2023 "Aluminum and aluminum alloy extruded profiles for general industrial use", the performance of the aluminum-based composite materials in Examples 1 to 3 was tested.

[0049] Table 1 shows the properties of the aluminum-based composite materials in Examples 1-3.

[0050] Table 1

[0051]

[0052] The present invention reasonably adjusts the content of each element in the aluminum alloy, the content of the strengthening particles and the processing technology, so that the material has higher strength and elastic modulus, and is suitable for fields with higher requirements for strength and elastic modulus.

[0053] According to the disclosure of the above description, those skilled in the art to which the present invention belongs may also make appropriate changes and modifications to the above embodiments. Therefore, the present invention is not limited to the specific embodiments disclosed and described above, and some modifications and changes to the present invention should also fall within the scope of protection of the claims of the present invention. In addition, although some specific terms are used in this specification, these terms are only for the convenience of description and do not constitute any limitation to the present invention.

Claims

1. A method for preparing an aluminum-based composite material, characterized in that: The method comprises: Weigh silicon carbide particles with a particle size of 0.1-1 mm and aluminum chips with a particle size of ≤5 mm in a mass ratio of (0.1-5): (95-99.9), wherein the aluminum chips include the following raw material components by mass percentage: Mg 0.9-1.5wt.%, Si 0.9-1.5wt.%, Cu0.6-1.1wt.%, Mn 0.01-0.15wt.%, Cr 0.01-0.15wt.%, Ti≤0.03wt.%, Fe≤0.10wt.%, and the balance is Al and unavoidable impurities; The aluminum chips and the silicon carbide particles are vibrated and mixed, and then the mixture is placed in a briquetting machine for high-temperature pressing to form aluminum rod blanks, and finally the aluminum rod blanks are placed in an extruder for hot extrusion.

2. The method for preparing the aluminum-based composite material according to claim 1, characterized in that: The mass ratio of Mn to Cr in the aluminum chips is (1-1.5):

1.

3. The method for preparing the aluminum-based composite material according to claim 1, characterized in that: The vibration mixing adopts a powder resonance mixer, and the vibration frequency of the powder resonance mixer is 20-30 Hz and the vibration time is 15-30 min.

4. The method for preparing the aluminum-based composite material according to claim 1, characterized in that: The specific process of placing the mixture in a briquetting machine and pressing it into aluminum rod blanks is as follows: a mixture of silicon carbide particles and aluminum chips is loaded into a mold of the briquetting machine. The pressure of the briquetting machine is 1-5 tons. The mold temperature during the pressurization process is 400-520°C and the pressurization time is 1-5 minutes.

5. The method for preparing the aluminum-based composite material according to claim 4, characterized in that: The hot extrusion process is as follows: placing an aluminum bar blank in an extruder, and extruding the aluminum bar blank under the conditions of an extrusion ratio of 15-30, an extrusion temperature of 540-570° C., and an extrusion speed of 2-4 m / min.

6. The method for preparing the aluminum-based composite material according to claim 1, characterized in that: The aluminum chips are vibrated and mixed with the silicon carbide particles after being degreased and deoiled. The aluminum chips degreasing and deoiling process is as follows: the aluminum chips are ultrasonically cleaned with a strong alkaline solvent, a surfactant and acetone in sequence, and finally cleaned with ethanol and dried for later use; the ultrasonic power during the ultrasonic cleaning is 100-500W, and the time is 10-30min.

7. An aluminum-based composite material, characterized in that: The aluminum-based composite material is prepared by the preparation method of any one of claims 1 to 6.

8. The aluminum-based composite material according to claim 1, characterized in that: The aluminum-based composite material has a yield strength of ≥400 MPa, an elastic modulus of ≥85 GPa, and a plasticity of ≥8%.

Citation Information

Patent Citations

  • Aluminum-based composite materials and their processing methods

    CN114934242A

  • Aluminum-based composite material and preparation method thereof

    CN119061283A

  • High-plasticity gadolinium-containing aluminum-based composite material as well as preparation method and application thereof

    CN119061284A

  • Reinforced aluminum-based composite material and preparation method thereof

    CN119082626A